Pembuatan Desain Shade House Untuk Pembibitan Bibit Kelengkeng Di Wisata Kampung Kelengkeng, Desa Simoketawang, Sidoarjo - Herlina Herlina; Febby Rahmatullah Masruchin; Yessi Maretha Miraningsih; Ulya Azizah; Fifa Marisa Irwayu; Rizki Dwi Rama Setyawan; Arifa Yuriyadi (PROSIDING SEMINAR NASIONAL PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2022)
Longan is a fruit that is much liked by the people of Indonesia. Several types of longan fruit circulating in the market are still obtained by importing, so the opportunity to cultivate longan in Indonesia is still high. Although most longans grow in the highlands, now many longans grow in the lowlands. Simoketawang Village Sidoarjo is located in the lowlands and in this village has longan village tourism that has the potential to be developed. One of the programs to support longan village tourism is the longan seed nursery. So far, longan seeds are obtained by buying and it is hoped that villagers will have the ability to do longan seedlings so they don't need to buy more and can even be sold to make a profit. The implementation of community service this time is aimed at the initial step of kengkeng seedling nursery, namely by making a shade house design for the seed house.